Teguran Malaikat Tuhan dan Pertobatan Bangsa Israel Historis Kritis Hakim-Hakim 2:1-5 - Rangga Abednego Simaremare; Tickos Elia Siahaan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research examines Judges 2:1-5 through a historically critical lens to explain their theological implications and relevance to contemporary audiences. The Book of Judges summarizes a pivotal period in Israel's historical narrative as they sought to defend their faith in the face of foreign cultural influences. This passage describes the warning of the Archangel of God to Israel for their failure to expel the Canaanites from the Promised Land, which had a detrimental effect on their religious and social dynamics. This analysis investigates historical context, literary composition, and symbolic elements, while also emphasizing central themes such as obedience to divine command, the impact of transgression, and the need for repentance. Using qualitative methodologies, including literary analysis and exegetical scrutiny, this study shows that loyalty to God is a prerequisite for receiving His help, while disobedience entails oppression and harmful influence. The continued relevance of this text serves as a poignant reminder of the necessity of upholding unwavering devotion to God in the midst of life's vicissitudes.